(untitled) (Journal of Science Foundation, 2013)
Chronic osteomyelitis is relatively unusual complication of intramedullary nail fixation of long bone fractures. Depending on the extent of infection, timing of diagnosis and progress of fracture healing, different treatment options have been developed. There is no hard and fast rule for the treatment of chronic osteomyelitis related to implant. Still now it is a big challenge for orthopaedic surgeons to handle such cases. Some options are very costly and time consuming. We are reporting here such a case of chronic osteomyelitis of femur fracture fixed with interlocking nail in a 23 year young man. His fracture was a closed one. Appropriate therapy for chronic osteomyelitis complicating a fracture is based on a multimodality approach even if there is no set algorithm to take in charge the two central problems related to it namely eradication of infection and fracture union. The surgical techniques and choice of fracture fixation determined according to age, weight, profession, intellectual status of patient and the expertise available. Clinical signs and investigation should alert the surgeon to the possibility of an underlying infection and appropriate measures should take quickly. It is important not to underestimate local skin irritation or signs of inflammation. DOI: http://dx.doi.org/10.3329/jsf.v11i1.19397